187k views
0 votes
What is the value of the expression? (9÷3)+4(6-7)

2 Answers

6 votes

Answer:

-1

Explanation:

According to PEMDAS, we must start with what's in the parenthesis:

(9/3)=3

and

(6-7)=-1

Which leaves us with the equation 3+4(-1)

The next step would be multiplication:

4(-1)=-4

Leaving us with 3+(-4), which simplifies to:

3-4=-1

Hope this helps!

User Alistaircol
by
5.6k points
0 votes

Explanation:

(9÷3)+4(6-7)

=(3)+4(1)

=3+4

=7

User Saravana Va
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.